2006
DOI: 10.1159/000094746
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of MRI to Demonstrate the Mechanisms of Myocardial Ischemia in Hypertrophic Cardiomyopathy with Myocardial Bridge

Abstract: We present a case of symptomatic primary hypertrophic cardiomyopathy (HCM) associated with myocardial bridging of the left anterior descending (LAD) artery and suspected ischemia that could be related either to LAD artery compression or to microvascular perfusion abnormalities. MRI demonstrated the morphological appearance of myocardial hypertrophy, and coronary MR angiography evidenced the myocardial bridge and its functional consequences with stress MR perfusion. In conclusion, as a non-invasive comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…12, together with the literature data in which irradiation temperature was below 623 K. 8,11,[21][22][23][24][25][26][27] A high density of fine bubbles similar to the present study was reported in HFIR and ATR irradiations. 22,23) In these data the diameter and number density were <3 nm and in the order of 10 23 m À3 , respectively. A common condition between these data and the present data appeared to be high helium generation.…”
Section: Cavitiessupporting
confidence: 87%
See 1 more Smart Citation
“…12, together with the literature data in which irradiation temperature was below 623 K. 8,11,[21][22][23][24][25][26][27] A high density of fine bubbles similar to the present study was reported in HFIR and ATR irradiations. 22,23) In these data the diameter and number density were <3 nm and in the order of 10 23 m À3 , respectively. A common condition between these data and the present data appeared to be high helium generation.…”
Section: Cavitiessupporting
confidence: 87%
“…[21][22][23] These were identified in all the irradiation conditions whereas no void was observed. The difference of 30 K (565 vs. 595 K in samples C vs. D and G vs. H) in similar dose and dose rate condition caused no notable changes in cavity morphology.…”
Section: Cavitiesmentioning
confidence: 89%
“…MDCT coronary angiography has been accepted for the noninvasive imaging technique of choice for the diagnosis of myocardial bridging. Other non-invasive imaging techniques for assessing ischemia, such as dobutamine magnetic resonance imaging (MRI), MRI stress perfusion, and myocardial perfusion SPECT may be helpful in the functional assessment of the significance of myocardial bridging [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in cardiac imaging with cardiac CT, cardiac MRI, can also be used in making the diagnosis [ 19 , 20 ]. Cardiac CT is an alternative for patients with a low pretest probability for coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%